PEMAHAMAN NASABAH TENTANG KONSEP MUDHARABAH (Studi Pada BMT Ditha Anugerah Abadi Makassar) - Rasulong, Ismail (Universitas Muhammadiyah Makassar, 2011)
This study aims to analyze the influence of product factors, religious factors, and social class factors on the understanding of BMT customers and to explain the dominant factor of influence on the understanding of BMT customers. This research is eksplanasi, data collection method is survey on selected respondents with the number of samples of 50 people. Data analysis using multiple regression. The results showed that product factors, religious factors, and social class factors have a significant positive effect on the understanding of BMT customers about the concept of mudaraba. All three factors have a strong correlation level to the understanding of customers with a determination of 58.5%. This means that these three factors are the decisive factors that can assist the customer in understanding the concept of mudaraba system. Further partially, there is one factor that is not siginfikan influence on customer understanding, while the other two factors namely product factors and religious factors have a significant positive effect. The effective contribution of these three factors is: religious factor contributes effectively to 20.2% of customer understanding, religious factor with effective contribution of 33.1%, and factor three is only 1.5%. based on partial test, it is known that religious factor is the most dominant factor affecting customers understanding.